Improve Integration of In Vitro Biofilm Body of Knowledge to Support Clinical Breakthroughs in Surgical Site Infection. (November 2021) - Irwin, Stuart; Mackenzie, Brett Wagner; Matthews, Brya G; Williams, Dustin L; Cornish, Jillian; Swift, Simon
Abstract : Prosthetics increase the risk of deep surgical site infections in procedures intended to restore function. In orthopaedics, prosthetic joint infections can lead to repetitive surgeries, amputation, or worse. Biofilm formation both in vitro and in vivo involves stages of attachment, accumulation, and maturation. The level of maturation affects susceptibility to antibiotics, the immune system, and the success of surgical interventions. A review of the literature indicates that orthopedic publications are less likely to mention biofilm. We have reviewed animal models of infection to assess in vivo models of prosthetic infection. Although most prosthetic infections seem to originate from local skin microbiota, clinically representative biofilm inocula are unusual. Biofilm-related end points are more widely adopted, but studies rarely include both quantification of adherent microbial burden and imaging of the in vivo biofilm. Failure to differentiate between planktonic and biofilm infections can skew research away from needed chronic disease models. In this review, we address prosthetic joint infections as an important model for chronic biofilm infection research, identify critical requirements for in vivo models of chronic infection, and propose that resistance to the terminology of biofilm research exists within both research and regulation, which could limit progress toward important orthopaedic targets.